2022
DOI: 10.21037/atm-22-1076
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a patient-derived organoid model and living biobank for nasopharyngeal carcinoma

Abstract: Background Recurrent nasopharyngeal carcinoma (NPC) remains a major challenge for clinicians and scientists. Tumor organoid is a revelational disease model that highly resembled the heterogeneity and histopathological characteristics of original tumors. This study aimed to optimize the modeling process of patient-derived NPC organoids (NPCOs), and establish a living-biobank of NPCs to study the mechanism and explore the more effective treatment of the disease. Methods S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…228 As mentioned previously, the PDX model provides a novel approach for identifying suitable alterations in tumor tissue to find promising treatment methods. [229][230][231][232] Recently, this model has been considered an ideal preclinical model for investigating targeted drugs. These PDX models maintained the genetic background in immunodeficient mice.…”
Section: Targeted Therapy In a Preclinical Model In Vivomentioning
confidence: 99%
“…228 As mentioned previously, the PDX model provides a novel approach for identifying suitable alterations in tumor tissue to find promising treatment methods. [229][230][231][232] Recently, this model has been considered an ideal preclinical model for investigating targeted drugs. These PDX models maintained the genetic background in immunodeficient mice.…”
Section: Targeted Therapy In a Preclinical Model In Vivomentioning
confidence: 99%
“…The high recurrence rate is responsible for the poor prognosis for most nasopharyngeal cancers 53 . Wang et al 54 established a PDTO biobank of 39 primary and recurrent nasopharyngeal carcinomas and found that all nasopharyngeal carcinomas carried Epstein-Barr virus and kept the virus expanding. Furthermore, their stem cell markers were expressed more in recurrent organoids than in primary.…”
Section: Overview Of Pdto Biobanksmentioning
confidence: 99%
“…To date, researchers have established live organoids for various tumors, including locally advanced rectal cancer ( 82 ), CRC, liver metastasis of CRC ( 80 ), breast cancer ( 83 ), bladder cancer ( 84 ), nasopharyngeal cancer ( 85 ), pancreatic cancer ( 86 ), non-small cell lung cancer ( 87 ), gastric cancer ( 88 ) and glioblastoma ( 89 ). For the first time, van de Wetering et al ( 41 ) successfully established a living biobank for CRC, including 22 tumor organoids and 19 normal adjacent organoids from 20 patients.…”
Section: Establishment Of a Living Biobank Of Crc Organoidsmentioning
confidence: 99%